Nello specchio del Rinascimento: Mappature di un mito storico-politico (Materiali di Estetica. Terza serie, 2022)
Today, historians, philosophers, and scholars of cultural heritage discuss about the relationship between the periodizing labels of historiography and their symbolic employment within the current political rhetoric. To understand the relevance of this issue in Italy, it can be helpful to look at the academic and public debates around the category of “Renaissance”. On the one hand, this article aims to map some notable political uses of this historical figure as a symbol; on the other hand, it reconstructs a tradition of thought focused on the epistemic autonomy of the same category. With these intentions, I look at a group of Italian critics of Johan Huizinga’s aesthetic view of history – like Delio Cantimori, Eugenio Garin, and their heirs within the academic milieu of the “Scuola Normale” of Pisa. Finally, I evaluate whether there is any correspondence between “Renaissance” as a symbol within the political debate and its historiographical employment as a periodizing label.
Keywords: Renaissance; Rhetoric; Historiography; Myth